Synthesis and Properties of 1H-Pyrrolo[3′,2′:3,4]fluoreno[9,1-gh]quinolines and 7H-Pyrrolo[2′,3′,4′:4,10]anthra[1,9-fg]quinolines - Aleksandra Khomutetckaia; Peter Ehlers; Alexander Villinger; Peter Langer (Molecules)
We report the synthesis of pyrrolo[3′,2′:3,4]fluoreno[9,1-gh]quinoline and pyrrolo[2′,3′,4′:4,10]anthra[1,9-fg]quinoline derivatives. This novel class of N-doped polycyclic heteroaromatic compounds was synthesized by a site-selective cross-coupling reaction followed by acid-mediated cycloisomerization and Pd-catalyzed CH arylation as the final ring-closing reactions. Preliminary optical and aromatic properties were studied by means of steady-state absorption and fluorescence spectroscopy and DFT calculation. Special emphasis was placed on the impact of ring alternation and position of the N-doping within the scaffold.